The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1161/jaha.113.000424
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Percutaneous Patent Ductus Arteriosus Closure: An Unselected Multicenter Population Experience

Abstract: BackgroundThe technique and safety of transcatheter patent ductus arteriosus (PDA) closure have evolved during the past 20 years. We sought to report a multicenter experience of PDA closure with a focus on the rate of adverse events (AE) and a review of institutional practice differences.Methods and ResultsOutcome data on transcatheter PDA closure were collected at 8 centers prospectively using a multicenter registry (Congenital Cardiac Catheterization Project on Outcome Registry). Between February 2007 and Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 14 publications
(21 reference statements)
4
49
2
Order By: Relevance
“…Although an exact lower weight limit for the safe closure of a PDA has not been established, previous studies have excluded preterm infants <4 kg or reported no cases of percutaneous PDA closure below this weight threshold 11, 12, 13, 14. While recent case reports suggest catheter‐based PDA closure is feasible among infants <4 kg,15, 16 data on the safety of the procedure, including adverse events beyond the immediate catheterization period (eg, posthospitalization), are lacking 17. Since very premature infants <4 kg are more complex and medically fragile than are their more mature counterparts,18 a separate consideration of the short‐ and long‐term risks and benefits of percutaneous PDA closure in this unique subgroup is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although an exact lower weight limit for the safe closure of a PDA has not been established, previous studies have excluded preterm infants <4 kg or reported no cases of percutaneous PDA closure below this weight threshold 11, 12, 13, 14. While recent case reports suggest catheter‐based PDA closure is feasible among infants <4 kg,15, 16 data on the safety of the procedure, including adverse events beyond the immediate catheterization period (eg, posthospitalization), are lacking 17. Since very premature infants <4 kg are more complex and medically fragile than are their more mature counterparts,18 a separate consideration of the short‐ and long‐term risks and benefits of percutaneous PDA closure in this unique subgroup is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Transcatheter closure of PDA is a safe and effective alternative therapeutic modality to surgical intervention . In large PDA of infants, there is a narrow margin of safety between undersized device (embolization, residual flow) and oversized device (PA or DTA obstruction) . Device selection is crucial with respect to type and size of the device.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous closure of the PDA is among the safest of interventional cardiac procedures and is considered to be the procedure of choice for PDA closure beyond infancy (≥5 kg) . Robust evidence among older and more mature patients has led investigators to study the feasibility and safety profile of catheter‐based interventions to close the PDA during infancy .…”
Section: Introductionmentioning
confidence: 99%